Sérgio Buarque de Holanda na USP - Sanches, Rodrigo Ruiz [UNESP] (FapUNIFESP (SciELO), 2011)
The main purpose of the article is to describe and to analyse Sérgio Buarque de Holanda's trajectory in Universidade de São Paulo (USP). At USP, he could dedicate himself entirely in what he liked to do: to research. There, Sérgio Buarque de Holanda formed a researchers' group and he changed the teaching routes in History course, which formed only Elementary and High School teachers. He idealized and founded the Instituto de Estudos Brasileiros (Brazilian Studies Intitute), a multi-disciplinary institution responsible for important researches included the theme Brasil. In this Institute (IEB), he formed a ample archive and a important library. In 1969, the 13-years-job at USP finished itself in a careworm process, when he asked for his retirement in sympathy with other retired professors compulsorily by AI-5.
Sérgio Buarque de Holanda at USP
Keywords: Intelectual independence; Sérgio Buarque de Holanda; Universidade de São Paulo